The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1108/mmms-09-2020-0230
|View full text |Cite
|
Sign up to set email alerts
|

The effect of manufacturing defects on the high-cycle fatigue of electron-beam-welded Ti-6Al-4V titanium alloy: experimental and numerical analysis

Abstract: PurposeElectron-beam welding has been widely used in industry to join different titanium alloys (Ti-6Al-4V) components. During welding production defects, such as porosity, lack of penetration or thinning are often observed. High-cycle fatigue (HCF) tests have been performed on welded specimens to understand the effect of weld defects on fatigue capabilities. The fatigue life of different types of “defective” welds has been compared against a non-welded reference specimen.Design/methodology/approachThe results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Recent studies on rotary Friction welding (RFW) of Grade 5 -Titanium alloy by Nu et al [16,17] has shown axial pressure to be the most influential factor for high tensile strength and hardness. Many researchers have reported the effect of heat treatments on mechanical properties of Grade 5 -Titanium alloy fusion welds [18][19][20], some on LFW of Grade 5 -Titanium alloy [21] and FSW [22]. In RFW of Grade 5 -Titanium alloy, heat treatment effects were not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on rotary Friction welding (RFW) of Grade 5 -Titanium alloy by Nu et al [16,17] has shown axial pressure to be the most influential factor for high tensile strength and hardness. Many researchers have reported the effect of heat treatments on mechanical properties of Grade 5 -Titanium alloy fusion welds [18][19][20], some on LFW of Grade 5 -Titanium alloy [21] and FSW [22]. In RFW of Grade 5 -Titanium alloy, heat treatment effects were not reported.…”
Section: Introductionmentioning
confidence: 99%
“…welding (Giannella et al 2017a;Fellinger et al 2018)) to the latest cutting-edge processes recently entering the industry (e.g. advanced welding procedures (Carlone et al 2016;Rubino et al 2020Rubino et al , 2021 or additive manufacturing (Caggiano et al 2019(Caggiano et al , 2021). Considering the inhomogeneous microstructure and non-uniform mechanical properties of metal materials, including crystal defects, grains boundary, dislocations, etc., cracks may encounter diversiform microstructures, in turn demonstrating variable strength against FCG.…”
mentioning
confidence: 99%